Pulmonale Hypertonie: was ist neu in der Therapie? - Sommer, Natascha; Weigand, Markus A. (Der Anaesthesist, 2016)
Pulmonary hypertension (PH) comprises a group of pulmonary vascular diseases that are characterized by progressive exertional dyspnea and right heart insufficiency ultimately resulting in right heart decompensation. The classification is into five clinical subgroups that form the absolutely essential basis for decisions on the indications for different pharmacological and non-pharmacological forms of treatment. The guidelines were updated in 2015 and in addition to the hitherto existing pharmacological treatment options of phosphodiesterase type 5 inhibitors, endothelin receptor antagonists and prostacyclins, the soluble guanylate cyclase stimulator riociguat has now been incorporated for treatment of certain forms of PH. This article provides an overview of the new treatment recommendations in the current guidelines, e. g. for PH patients who are in intensive care units due to surgical interventions or progressive right heart insufficiency.